2003
DOI: 10.1002/ana.10655
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse models of dopamine deficiency

Abstract: The dopamine system is implicated in several neurological and psychiatric disorders. Genetic mutations or variations that affect dopamine system functions either directly cause or contribute to these disorders, even though other genetic and environmental factors may contribute significantly to some of these disorders as well. Transgenic mice increasingly become important tools in revealing functions of genes that are essential components of the dopamine system as well as in modeling human genetic disorders. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 105 publications
0
15
0
1
Order By: Relevance
“…DRD2, mRNA however, when knocked-out, has been shown to reduce fertility greatly (Chen and Zhuang 2003). Gevry et al (2006) had found elevated levels of the long and short forms of the DRD2 in Npc1 -/-mice, using a semi-quantitative method, while we found mildly decreased levels of total receptor using a quantitative method.…”
Section: Discussionmentioning
confidence: 48%
“…DRD2, mRNA however, when knocked-out, has been shown to reduce fertility greatly (Chen and Zhuang 2003). Gevry et al (2006) had found elevated levels of the long and short forms of the DRD2 in Npc1 -/-mice, using a semi-quantitative method, while we found mildly decreased levels of total receptor using a quantitative method.…”
Section: Discussionmentioning
confidence: 48%
“…The process of neurotransmission, however, requires other steps including storage in presynaptic nerve vesicles, release, interaction with receptors, and reuptake. In most animal models where each of these steps has been knocked out, the intracellular (and presumably extracellular) concentrations of neurotransmitters are profoundly changed (67)(68)(69)(70)(71). It is certain that these disorders occur in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Antidopamin adalah bahan kimia yang dapat menghentikan kerja dopamin (prolactin-inhibiting factor, prolactin-inhibiting hormone, prolactostatin) yaitu neurotransmitter yang berperan dalam menghambat pematangan gonad udang (Chen & Zhuang, 2003) dan menghambat pelepasan prolaktin pada mamalia. Aplikasi kombinasi GTH dan AD sebagai pengganti ablasi pada udang windu alam perlu dilakukan untuk mengetahui efek hormon ini terhadap pematangan dan produksi naupli.…”
Section: Pendahuluanunclassified